Portable Electrochemical Sensing System Attached to Smartphones and Its Incorporation with Paper-based Electrochemical Glucose Sensor - Takuya Fujimoto; Shogo Kawahara; Yukio Fuchigami; Shoji Shimokawa; Yosuke Nakamura; Kenichi Fukayama; Masao Kamahori; Shigeyasu Uno (International Journal of Electrical and Computer Engineering (IJECE), 2017)
This paper described the development of a small and low cost biosensor consisting of a smartphone-based electrochemical biosensor device and a paper-based biosensor. The device harvested power from the smartphone and transferred data through audio jack. We designed CMOS circuits including a power supply circuit, a potentiostat, and a ΔΣ modulator. The fabrication of a paper-based biosensor was simple: the three electrodes were directly drawn on chromatography paper using a carbon pencil. The paper-based biosensor was low cost, disposable, portable and friendly to the environment. The sensing system was designed to perform the chronoamperometry measurement, and the glucose concentration in a liquid specimen was detected. Results showed that the sensing system was capable of measuring the glucose concentration as precisely as expensive equipments.